The Global Burden of Disease Study Estimates of Brazil's Cervical Cancer Burden - Nathalia V. S. Reis; Brenda B. Andrade; Maximiliano R. Guerra; Maria Tereza B. Teixeira; Deborah C. Malta; Valéria M. A. Passos (Ubiquity Press, 2020)
Background: Cervical cancer represents an important preventable cause of morbidity and mortality in developing countries such as Brazil. Investigating temporal evolution of a disease burden in the different realities of the country is essential for improving public policies. Objective: To describe the national and subnational burden of cervical cancer, based on the estimates of the 2017 Global Burden of Disease study. Methods: Descriptive study of premature mortality (years of life lost [YLL]) and burden of disease (disability-adjusted life years [DALYs]) associated with cervical cancer among Brazilian women aged 25-64 years, between 2000 and 2017. Findings: During the study period, age-standardized incidence decreased from 23.53 (22.79-24.26) to 18.39 (17.63-19.17) per 100,000 women, while mortality rates decreased from 11.3 (11.05-11.56) to 7.74 (7.49-8.02) per 100,000 women. These rates were about two to three times greater than equivalent rates in a developed country, such as England: 11.98 (11.45-12.55) to 10.37 (9.85-10.9), and 3.75 (3.68-3.84) to 2.82 (2.75-2.9) per 100,000 women, respectively. Poorer regions of Brazil had greater rates of the disease; for instance, Amapá State in the Northern Region had rates twice as high as the national rates during the same period. Cervical cancer was the leading cause of premature cancer-related mortality (YLL = 100.69, 91.48-110.61 per 100,000 women) among young women (25-29 years) in Brazil and eight federation units of all country regions except the Southeast in 2017. There was a decrease in the burden of cervical cancer in Brazil from 339.59 (330.82-348.83) DALYs per 100,000 women in 2000 to 238.99 (230.45-247.99) DALYs per 100,000 women in 2017. Conclusion: Although there has been a reduction in the burden of cervical cancer in Brazil, the rates remain high, mainly among young women. The persistence of inequalities between regions of Brazil suggests the importance of socioeconomic determinants in the burden for this cancer.